Reactions to Irish nationalism - O'Day, Alan (Hambledon Press, 1987)
From the mid-3961s to 3936 the Irish problem was frequently the prime issue in British politics. Quantatively it absorbed more time and energy than any other question. There was little about Ireland which was not aired at length in the press, in Parliament and at the dinner tables of the British political elite. Fenianism obsessed British minds at the beginning of the period while at the end it seemed all too possible that Irish home rule would spark off the largest civil disruption in the British Isles since the seventeenth century. Throughout the late Victorian and Edwardian eras Ireland nev.